2011
DOI: 10.1371/journal.pone.0027844
|View full text |Cite
|
Sign up to set email alerts
|

Antimycotic Ciclopirox Olamine in the Diabetic Environment Promotes Angiogenesis and Enhances Wound Healing

Abstract: Diabetic wounds remain a major medical challenge with often disappointing outcomes despite the best available care. An impaired response to tissue hypoxia and insufficient angiogenesis are major factors responsible for poor healing in diabetic wounds. Here we show that the antimycotic drug ciclopirox olamine (CPX) can induce therapeutic angiogenesis in diabetic wounds. Treatment with CPX in vitro led to upregulation of multiple angiogenic genes and increased availability of HIF-1α. Using an excisional wound sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Current topical formulations of ciclopirox olamine used to treat fungal skin infections and vaginal candidiasis penetrate deep into the skin and mucosal membranes without causing adverse systemic reactions [10]. It has already been shown that ciclopirox olamine applied topically to wounds induces angiogenesis and promotes faster wound healing [13]. Thus the excellent tolerability of ciclopirox and its unique mode(s) of action make it an attractive antibiotic to treat gram-negative pathogens, including those resistant to current antibiotic therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current topical formulations of ciclopirox olamine used to treat fungal skin infections and vaginal candidiasis penetrate deep into the skin and mucosal membranes without causing adverse systemic reactions [10]. It has already been shown that ciclopirox olamine applied topically to wounds induces angiogenesis and promotes faster wound healing [13]. Thus the excellent tolerability of ciclopirox and its unique mode(s) of action make it an attractive antibiotic to treat gram-negative pathogens, including those resistant to current antibiotic therapies.…”
Section: Discussionmentioning
confidence: 99%
“…No fungal resistance has been identified in over twenty years of clinical use [10]. Indeed, others have suggested repurposing ciclopirox as an anti-human immunodeficiency virus drug [11], an agent to protect against mitochondrial damaged cells [12], and a way to enhance diabetic wound healing [13]. Additionally, ciclopirox is currently in a Phase I clinical trial for treatment of multiple myeloma [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ciclopirox may be repurposed as an anti-human immunodeficiency virus drug, 8 a protective agent against mitochondrial cell damage, 9 or a promoter of diabetic wound healing. 10 Very recently, ciclopirox was also suggested as a repurposed bacteriostatic antibiotic for gram-negative bacteria. 11 Ciclopirox affects galactose metabolism and alters the composition of lipopolysaccharide (LPS), 11 a target of polymyxin B.…”
mentioning
confidence: 99%
“…This increase in collagen deposition was unexpected, as the prolyl hydroxylase inhibitor CPX is known to cross‐inhibit collagen prolyl hydroxylases, which would predict reduced collagen secretion and deposition . In fact, granulation tissue increase had not been reported upon treatment of diabetic murine wounds with high dose 50 mM of CPX as the sole drug …”
Section: Discussionmentioning
confidence: 99%